Does spending time outdoors reduce stress? A review of real-time stress response to outdoor environments. (May 2018) - Kondo, Michelle C.; Jacoby, Sara F.; South, Eugenia C.
Abstract: Everyday environmental conditions impact human health. One mechanism underlying this relationship is the experience of stress. Through systematic review of published literature, we explore how stress has been measured in real-time non-laboratory studies of stress responses to deliberate exposure to outdoor environments. The types of exposures evaluated in this review include: nature viewing, outdoor walks, outdoor exercise and gardening. We characterize study design, modalities of stress measurements, and statistical estimates of effect and significance. Heart rate, blood pressure, and self-report measures provide the most convincing evidence that spending time in outdoor environments, particularly those with green space, may reduce the experience of stress, and ultimately improve health. More work is needed to understand effects of in situ modifications to outdoor environments on residents' stress response. Highlights: Systematic review of 43 real-time non-laboratory studies of stress responses to outdoor, often natural, environments. Stress outcome measurements were by anthropometric instruments, saliva, blood, urine, actigraph, self-report and eeg. Environmental exposures included nature viewing, outdoor walk, outdoor exercise, or gardening. Heart rate, blood pressure, and self-report results provide the most convincing evidence.